Bariatric surgery in University Clinical Centre Tuzla and Bosnia and Herzegovina: where we are and where we want to be - Fuad Pašić; Nermin Salkić; Emir Ahmetašević; Ervin Alibegović; Jasmina Smajić; Lejla Jašarević; Rusmir Softić; Jasmin Hamidović; Amina Krupalija (Medicinski glasnik, 2025)
Bariatric surgery has emerged as the most effective treatment for morbid obesity, offering substantial and sustained weight loss and improvement in comorbid conditions. This paper reviews the development, implementation, and outcomes of bariatric surgery at the University and Clinical Centre Tuzla based on a retrospective analysis of patients who underwent bariatric surgery over a three-year period. A significant weight loss was observed, postoperative complications were minimal, with no in-hospital mortality. The bariatric surgery program demonstrates a significant progress in treating morbid obesity in Bosnia and Herzegovina.
Keywords: complica-tions; retrospec-tive anal-ysis; weight loss